2018
DOI: 10.1093/aje/kwy258
|View full text |Cite
|
Sign up to set email alerts
|

Shift Work and Respiratory Infections in Health-Care Workers

Abstract: Recently, there has been interest in whether shift work may enhance susceptibility to infection. Our aim was to determine whether shift workers in the health-care field have a higher incidence, duration, and/or severity of influenza-like illness (ILI) and acute respiratory infection (ARI) than non–shift workers. From September 2016 to June 2017, 501 rotating and/or night-shift workers and 88 non–shift workers from the Klokwerk+ Study (the Netherlands, 2016–2017) registered the occurrence of ILI/ARI symptoms da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 31 publications
3
54
0
2
Order By: Relevance
“…Correspondingly, prior work found shift work to be associated with increased infection susceptibility (Cuesta et al 2016;Mohren et al 2002). A recent study of our group suggested that, compared to non-shift workers, shift workers in healthcare have a 20% higher incidence of respiratory infections, and a 22% higher incidence of severe respiratory infections (Loef et al 2019).…”
Section: Introductionmentioning
confidence: 58%
See 3 more Smart Citations
“…Correspondingly, prior work found shift work to be associated with increased infection susceptibility (Cuesta et al 2016;Mohren et al 2002). A recent study of our group suggested that, compared to non-shift workers, shift workers in healthcare have a 20% higher incidence of respiratory infections, and a 22% higher incidence of severe respiratory infections (Loef et al 2019).…”
Section: Introductionmentioning
confidence: 58%
“…As reported, the results suggest that when a respiratory infection is present, shift workers are not more or longer absent than non-shift workers. Nevertheless, as shift workers were found to have a higher incidence rate of respiratory infection episodes (Loef et al 2019 , Table 1), a similar sickness absenteeism rate due to respiratory infections might suggest that shift workers are cumulatively (e.g., during an entire winter season) more often absent than non-shift workers. For example, if shift workers as well as non-shift workers are on average absent during approximately 15% of the ILI/ARI episodes (Table 2), but shift workers report 20% more ILI/ARI episodes per winter season (Loef et al 2019), than the total number of absenteeism spells will be higher in shift workers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since circadian rhythm disruption may impair immune system function, some scholars sustained that it could enhance susceptibility to infection [5,6]. A recent prospective cohort study showed that shift workers in healthcare had 20% more acute respiratory infection and influenza-like illness than non-shift workers [7]. These infections also appeared to be more severe also.…”
Section: Accepted Manuscriptmentioning
confidence: 99%